2009
DOI: 10.1074/jbc.m109.006098
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C-γ Binds Directly to the Na+/H+ Exchanger 3 and Is Required for Calcium Regulation of Exchange Activity

Abstract: Multiple studies suggest that phospholipase C-␥ (PLC-␥) contributes to regulation of sodium/hydrogen exchanger 3 (NHE3) in the small intestine, although the mechanism(s) for this regulation remain unknown. We demonstrate here that PLC-␥ binds directly to the C terminus of NHE3 and exists in similar sized multiprotein complexes as NHE3. This binding is dynamic and decreases with elevated [Ca 2؉ ] i . The PLC-␥-binding site in NHE3 was identified (amino acids 586 -605) and shown to be a critical regulatory domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Elevation of free intracellular Ca 2ϩ by ionophore (4-bromo-A23187) or induced by carbachol (M3 cholinergic receptor mediated) inhibits NHE3 activity (9,17,24,26,28,52,54). Previous studies have shown that NHE3 inhibition by elevated Ca 2ϩ in PS120 cells requires NHERF2 but not NHERF1 (17).…”
Section: Expression Of Nhe3 In Caco-2/bbe Cellsmentioning
confidence: 96%
“…Elevation of free intracellular Ca 2ϩ by ionophore (4-bromo-A23187) or induced by carbachol (M3 cholinergic receptor mediated) inhibits NHE3 activity (9,17,24,26,28,52,54). Previous studies have shown that NHE3 inhibition by elevated Ca 2ϩ in PS120 cells requires NHERF2 but not NHERF1 (17).…”
Section: Expression Of Nhe3 In Caco-2/bbe Cellsmentioning
confidence: 96%
“…Also, Ca 2ϩ via PLC-␥ has been shown to inhibit NHE3 in fibroblasts. 38 These discrepancies could be either because of a difference in the cell system used or in response to various hormones used to increase Ca 2ϩ signaling and/or isoformspecific PLC activation. Our data suggest that, in proximal tubules, Ang II increases intracellular Ca 2ϩ , causing tyrosine phosphorylation/activation of Jak2, which, in turn, phosphorylates CaM.…”
Section: Discussionmentioning
confidence: 99%
“…The more consistent characteristics of NHE3 include the following: 1) it is activated under basal conditions, 2) under basal conditions, NHE3 interacts with Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), 3) only the γ isoform of this kinase associates with NHE3, 4) the NHE3 C-terminal domain, which is necessary for CaMKII binding under basal conditions, is 586-605 aa long and was predicted using multiple modeling programs to be α-helical, and 5) binding is rapidly reduced under conditions involving elevated physiological levels of Ca 2+ [13]. However, other proteins associate with NHE3, including NHERF1-4, phospholipase Cγ, and CK2α [43,44]. In addition, the CaMKII-mediated inhibition of basal NHE3 activity is NHERF2-dependent, occurs as a result of changes in the NHE3 turnover number and is associated with the phosphorylation of NHE3.…”
Section: Nhe3mentioning
confidence: 99%
“…This binding is rapidly reduced by a discrete increase in [Ca2+]i, which causes a conformational change in CaMKII that allows high-affinity interactions with target proteins and prevents the inactivation of the kinase by re-association between the catalytic domain and the autoinhibitory domain after Ca 2+ returns to basal levels [13,47,48]. Other proteins that associate with NHE3 require this NHE3 domain, and these include NHERF1-4, phospholipase Cγ and CK2α [43,44]. The CaMKII-mediated inhibition of basal NHE3 activity is NHERF2-dependent, modifies NHE3 turnover rates, and causes the phosphorylation of NHE3.…”
Section: Avp Receptors Involved In Distal Nephron Hco3-transportmentioning
confidence: 99%